Sosialisasi dan Penerapan Edinburgh Postnatal Depression Scale oleh Bidan dalam Upaya Deteksi Dini Depresi Ibu Postpartum di Muaro Jambi 2022 - Diniyati Diniyati; Pauline Kusmaryati; Imelda Imelda (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Postpartum depression is a mood disorder that occurs after childbirth and reflects psychological dysregulation which is a sign of major depressive symptoms. Objective To provide knowledge, skills and understanding of the Edinburgh Postnatal Depression Scale (EPDS) for midwives in the working area of Penyengat Olak Village, Kab. Muaro Jambi. Methods: used in this community service are lectures, modules, and questions and answers. This community service activity is the dissemination and application of the Edinburgh Postnatal Depression Scale (EPDS) to midwives in the work area of Penyengat Olak Village, Kab. Muaro Jambi. The results obtained in this community service are that the success of this community service activity is evaluated based on the level of filling out the Edinburgh Postnatal depression scale questionnaire and the service team evaluates by assessing the post test on the questionnaire. There is an increase in knowledge from 75% to 100%. The conclusion of this community service is that knowledge and understanding of participants about the Edinburgh Postnatal Depression Scale increases, the skills of participants in socializing about the Edinburgh Postnatal Depression Scale increase